Bioinformatics education in an MLIS program: the McGill experience - Joan C Bartlett (Journal of the Canadian Health Libraries Association, 2005)
Program objective The objective of this course (GLIS691 Bioinformatics) was to provide formal bioinformatics education within a master of library and information studies (MLIS) program. As bioinformatics becomes increasingly integral to biomedical research, there is a need for librarians to expand their practice into the domain of bioinformatics, supporting the efficient and accurate use of these complex resources. We developed this course, the first such course offered in a Canadian library school, in response to the demand for librarians to be able to support bioinformatics information needs. Setting The course was offered in the winter term of 2005 in the Graduate School of Library and Information Studies, McGill University. Participants Course participants were MLIS students. Program The course took a library and information science perspective to bioinformatics. The goal was to provide students with the skills and knowledge to provide information services in the domain of bioinformatics and to collaborate in the design and development of bioinformatics resources. This included understanding the field of bioinformatics and the range of resources, the needs and requirements of user groups, practical searching skills, the creation of resources, and the role of the librarian. Conclusions This course represents one approach to providing formal bioinformatics education for librarians. Librarians who are knowledgeable and proficient in bioinformatics will be able to expand the role of the library into this domain; apply their knowledge, skills, and expertise in a complex, chaotic information environment; and develop the essential role of the librarian in the domain of bioinformatics.